If Money Talks, What does it Say? : Corruption and Business Financing of Political Parties - McMenamin, Iain (Oxford Oxford University Press, 2013)
Why do businesses contribute to political parties? Is money a universal language? Do business contributions to political parties convey different messages in different countries? This book answers these questions based on intensive case studies of Australia, Canada, and Germany
Include Reference and Index
Keywords: Lobbying -- Political corruption -- Campaign funds